Framework for describing community integration for people with acquired brain injury - Parvaneh, Shahriar; Cocks, Errol (Wiley-Blackwell Publishing Asia, 2012)
Background/aim: Community integration is the ultimate goal of rehabilitation of adults with acquired brain injury which has a high incidence in the Australian population. The literature shows a need for a more comprehensive framework for community integration. This study developed a descriptive community integration framework drawn from views of five stakeholder groups and was compared with four similar frameworks. Methods: Thirty-seven experts in acquired brain injury, including practitioners, researchers, policy makers, people with acquired brain injury and family members participated. Using a Delphi method, an iterative process of surveys, interviews, and focus groups sought their views on community integration. Responses were analysed in three stages systematically to reduce a large quantity of raw data into a core set of descriptive themes. A final member checking process rated participants’ agreement with the importance of each theme. Results: Seven themes were identified and described: Relationships, Community Access, Acceptance, Occupation, Being at Home, Picking up Life Again, and Heightened Risks and Vulnerability. Themes were congruent with elements of the frameworks from the literature. Conclusions: Rich data came from the diverse stakeholders in the participant groups. Two unique themes reflected the importance of re-integration and recovering important aspects of previous lives, and identifying risks and vulnerabilities and providing safeguards. The framework reflected emphases that may be specific to acquired brain injury. It can be used as a basis for development of community integration programmes and outcome measures.